Metabolism-related hepatokines change in biliary atresia: ANGPTL6 as a potential biomarker - Daiqiong Fang; Shuqi Hu; Jinfa Tou; Fengqin Dong; Shiqiao Peng (BMC Pediatrics)
Abstract Objectives Biliary atresia (BA) is a severe obstructive cholangiopathy of early infancy that progresses to end-stage liver disease without any intervention. The aim of this study was to investigate the impact of drainage obstruction of bile on metabolism-related hepatokines and identify clinical biomarkers of BA. Methods A total of 38 patients with BA and 12 age-matched controls were recruited. Blood samples were obtained for measuring liver function and hepatokine levels. Linear correlations between these changes in hepatokines and bilirubin/bile acid were subsequently examined to explore the hepatokines that may reflect the illness severity. Afterwards, ROC curve analysis was conducted to assess the diagnostic value of the hepatokines. Finally, prognostic analysis of the hepatokines was performed based on early cholangitis, the clearance of jaundice, native liver survival and liver transplantation. Results The serum concentrations of TB, DB, ALT, AST, GGT, ALP and TBA in patients with BA were all increased compared with those in controls (P < 0.05). The plasma levels of ANGPTL4, HGF, FABP1, FGF21 and FGF23 were elevated in BA patients (P < 0.05), whereas the plasma ANGPTL6 level was decreased in BA patients (P < 0.05). The results of the correlation analysis revealed that ANGPTL6 was negatively linearly correlated with TB and DB and that FGF23 was positively linearly correlated with TBA. ROC curve analysis revealed that the AUC of ANGPTL6 for diagnosing BA was 0.9693, with a sensitivity of 0.8684 and a specificity of 1.0 at an optimal cut-off value of 1140.76 ng/ml. Prognostic analysis revealed that a lower plasma level of ANGPTL6 at KPE was associated with the occurrence of early cholangitis after KPE (P < 0.05). Conclusions Among all of the hepatokines that were measured in this study, ANGPTL6 may be a potential diagnostic biomarker of BA and may be able to predict the occurrence of early cholangitis. Clinical trial number : Not applicable.